Impact of engaging security personnel on access and polio immunization outcomes in security-inaccessible areas in Borno state, Nigeria - Nkwogu, Loveday; Shuaib, Faisal; Braka, Fiona; Mkanda, Pascal; Banda, Richard; Korir, Charles; Bawa, Samuel; Mele, Sule; Saidu, Mahmud; Mshelia, Hyelni; Shettima, Aliyu; Tegegne, Sisay G.; et al. (BMC public health, 2018)
Nigeria was polio free for almost 2 years but, with the recent liberation of areas under the captivity of insurgents, there has been a resurgence of polio cases. For several years, these inaccessible areas did not have access to vaccination due to activities of Bokoharam, resulting in a concentration of a cohort of unvaccinated children that served as a polio sanctuary. This article describes the processes of engagement of security personnel to access security-compromised areas and the impact on immunization outcomes. We assessed routine program data from January 2016 to July 2016 in security-inaccessible areas and we evaluated the effectiveness of engaging security personnel to improve access to settlements in security-compromised Local Government Areas (LGAs) of Borno state. We thereafter evaluated the effects of this engagement on postcampaign evaluation indicators. From 15 LGAs accessible to vaccination teams in January 2016, there was a 47% increase in July 2016. The number of wards increased from 131 in January to 162 in July 2016, while the settlement numbers increased from 6050 in January to 6548 in July 2016. The average percentage of missed children decreased from 8% in January to 3% in July 2016, while the number of LGAs with ≥ 80% coverage increased from 85% in January to 100% in July 2016. The engagement of security personnel in immunization activities led to an improved access and improvement in postcampaign evaluation indicators in security-compromised areas of a Nigerian state. This approach promises to be an impactful innovation in reaching settlements in security-compromised areas.